Comparison Between Minimally Invasive Anterolateral and Conventional Posterior Hip Approaches for Hemiarthroplasty in Hip Fractures - Rojcharoenngam, MD, Pranpawee (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: To compare the results between minimally invasive anterolateral and conventional posterior hip approaches for hemiarthroplasty in hip fractures. Methods: The elderly patients who had undergone hip hemiarthroplasty for hip fractures in Maharaj Nakhon Si Thammarat Hospital, were randomly divided into two groups: minimally invasive anterolateral and posterior approach groups Data were collected from March 2020 to November 2021, which included the duration of the surgery, length of the surgical wound, intraoperative bleeding volume, postoperative days of walking with a walker, morphine dosage for pain relief, and postoperative complications. Results: No significant difference (P-value > 0.05) was found between the baseline data of patients in both the groups, which included sex, age, body mass index, underlying musculoskeletal disease, and drug usage. The minimally invasive anterolateral approach group used an average surgical time of 53.48 ± 8.22 min, while the conventional posterior approach group required 65 ± 20.41 min; the length of the surgical wound was 7.78 ± 0.87 and 13.78 ± 1.37 cm, respectively; the volume of intraoperative bleeding was 82.17 ± 48.94 and 195.65 + 163.24 ml, respectively; the postoperative days of walking with a walker were 3.09 ± 0.92 and 6.59 ± 2.52 days, respectively; and the postoperative analgesic doses of morphine were 6.59 ± 2.80 and 11.09 ± 3.89 mg, respectively. The blood transfusion was required in 4 patients in the minimally invasive anterolateral approach group, while it was required in 14 patients in the conventional posterior approach group. Statistically significant (P-value < 0.05). Postoperative complications included, prosthetic hip joint dislocation in a patient in each group and sciatic nerve neurapraxia in a patient in the conventional posterior approach group. Conclusions: Hip hemiarthroplasty with the minimally invasive anterolateral approach in elderly patients with hip fractures was found to be superior to the conventional posterior approach.